Aquatic Environment and Toxicology - Burns, Corey (United States : ED-Tech Press, 2021)
Pollution of Aquatic systems (Examples: lakes, rivers, oceans, aquifers and groundwater) by large amounts of waste material that modify the water in negative fashion is termed as Aquatic Pollution. This type of ecological deprivation occurs when harmful pollutants are directly or indirectly discharged into aquatic systems without removal of harmful compounds. Aquatic pollution directly leads to suffering of organisms and vegetation that survive in water, including amphibians. Modern toxicology goes beyond the study of the adverse effects of exogenous agents by assimilating knowledgeand techniques from most branches of biochemistry, biology, chemistry, genetics, mathematics, medicine, pharmacology, physiology, and physics and applies safety evaluation and risk assessment to the discipline. In all branches of toxicology, scientists explore the mechanisms by which chemicals produce adverse effects in biological systems. Activities in these broad subjects complement toxicological research, thereby contributing to the application of this knowledge to the science and art of toxicology. The present book mainly deals with aquatic environmental, aquatic pollution, environmental toxicology and updates the subject matter, illustrations and problems to incorporate new concepts and issues related to aquatic ecosystem and environmental toxicology. The approach to presenting this book is traditional covering of environmental pollution, aquatic ecosystem and environmental toxicology.
Includes index.
Original publishing : 2018, reprinted 2021.
Includes bibliographical references.
Keywords: Environmental toxicology; Aquatic organisms -- Environmental aspects; Water quality -- Measurement; Selenium -- Environmental aspects; Environmental health